Penegakkan Hukum Pidana Dalam Rangka Penanggulangan Perjudian di Masyarakat - Hendrich Juk Abeth; Esti Royani; Salmonius (LPPM STIH Awang Long, 2021)
Indonesia is a state based on law (rechsstaat) and not a state based on power (machsstaat). Every act and behavior must be based on the applicable legal rules without discrimination. The purpose of this study is to find out how the policy of criminal law enforcement in the context of combating gambling in the community. This type of research is a normative juridical law research that is descriptive in nature so it does not test a hypothesis. Collecting data using literature study. Based on the results of the study, it was concluded that the crime of gambling is a form of crime in the field of decency whose punishment is not only imprisonment/imprisonment and fines, but also additional crimes such as revocation of the right to exercise the profession to the makers of gambling crimes in carrying out their profession. Every form of gambling crime, not only individuals but corporations are also held criminally responsible, and in sentencing the balance of individual interests and the interests of society must be considered.